Impact of crop commercialization on multidimensional poverty in rural Ethiopia: propensity score approach - Eyasu, Anteneh Mulugeta; Zewotir, Temesgen; Dessie, Zelalem G. (Frontiers in Public Health, 2025)
IntroductionReducing poverty through crop commercialization is one of the antipoverty efforts that helps promote health. This study explored the prevalence and the causal relationship between crop commercialization and rural Ethiopian households’ multidimensional poverty using multilevel data.MethodsThe study uses data from the most recent nationally representative Ethiopian socioeconomic survey 2018/19 to calculate the rural multidimensional poverty index using the Alkire and Foster technique. The data show 2,714 rural households nested in 59 administrative zones of Ethiopia. Based on several parameters (nutrition and health, education, living standards, rural livelihoods and resources, and risk), the investigation looks into the multidimensional poverty levels of Ethiopian rural households and how they differ across Ethiopian administrative zones.ResultsThe results indicate that 47.8% of the rural households of Ethiopians were multidimensionally poor in several dimensions; nutrition and health, education, living standards, rural livelihoods and resources, and risk. The living standard dimension is most deprivation-prone for the rural, multidimensional poor households. In addition, multidimensional poverty is more prevalent in Somali and Afar region rural areas. The best linear unbiased prediction estimates of multidimensional poverty vary substantially across Ethiopia’s administrative zones. Specifically, the top poorest performing administrative zones concerning the likelihood of being multidimensional poor among rural households were Shebelle, Zone 2, Zone 3, Zone 4, and Konso special woreda.ConclusionThe results of the generalized linear mixed-effects model show that crop-commercialized households have reduced the odds of being multidimensionally poorer than those who did not. This study recommends policymakers focus on rural mumyltidimensional poverty reduction strategies.